Effects of nursery diets on growth of pigs to market weight - Hancock, Joe D.; Mills, C.G.; Nichols, David A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effects of nutrient concentrations and complexity of ingredients used in nursery diets on growth performance to market weight. In Experiment 1, nursery regimens were: 1) simple ingredients/low lysine (corn-soybean meal-dried whey-based diet with 1.25% lysine for d 0 to 23 and a corn-soybean meal-based diet with 1.1% lysine for d 23 to 37) and 2) complex ingredients/ high-lysine (blood products, lactose, and other specialty ingredients with 1.5% lysine for d 0 to 9 and 1.25% lysine for d 9 to 23, and a corn-soybean meal-based diet with 1.1% lysine for d 23 to 37). In general, feed intake and rate of gain were increased for pigs fed the complex/high-lysine regimen. This improved performance resulted in an average advantage of 5 lb/pig at the end of the nursery phase. For the growing-finishing phase, pigs from the simple/low-lysine and complex/high-lysine nursery regimens were assigned to either a 2-step (.8 and .6% lysine to 150 and 250 lb, respectively) or 4-step (.95, .8, .75, and .6% lysine to 100, 150, 200, and 250 lb, respectively) regimen and fed to a market wt of 250 lb. Pigs fed the 4-step regimen had greater rate of gain, but there was no complementary effect of the complex high-lysine regimen in the nursery phase with the 4-step regimen in the growing- finishing phase. We should note, however, that there was also no compensatory response of the pigs fed the simple/lowlysine diet in the nursery phase when given either the 2-step or 4-step regimen during growing-finishing. The net result was that the 5 lb difference at the end of the nursery phase resulted in an additional 3.6 d required for pigs fed the simple/low-lysine regimen to reach a market wt of 250 lb. In Experiment 2, the same diet regimens were used except that a third diet, with 1.5% lysine (resulting from adding wheat gluten and crystalline lysine) was added to the simple nursery regimen. Pigs fed the complex nursery regimen generally had greater feed intake and rate of gain, resulting in a 3 lb/pig advantage at the end of the nursery phase. As in Experiment 1, there were no nursery regimen × grow-finish regimen interactions that would indicate compensatory gain, with 1.8 additional days required to reach the 250 lb market weight for pigs fed the simple nursery regimen. In conclusion, the combined results of both experiments indicated that for each 1 lb advantage at the end of the nursery phase, days to a market wt of 250 lb were reduced by .6 to .7 d.
Keywords: Swine; Compensatory gain; Diet complexity; Grow-finish; Lysine; Nursery